2020
DOI: 10.1111/ina.12762
|View full text |Cite
|
Sign up to set email alerts
|

Associations between household incense burning and delayed motor development among preterm infants modified by gestational age and maternal educational status

Abstract: Background: Household incense burning is a common ritual behavior in the Asia-Pacific region but has been associated with inferior developmental outcomes in term infants. We aimed to examine these associations among preterm infants. Methods: Information from 1190 mother-infant pairs during 6-and 18-month follow-up to the Taiwan Birth Cohort Study was examined for associations between household incense burning exposure and infant neurodevelopmental milestone achievement using multivariable Cox proportional haza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 52 publications
(137 reference statements)
2
7
0
Order By: Relevance
“…In the present study, children who occasionally and frequently exposed to incense fume performed inferior performance on executive function than nonusers. The findings of our study combining the results of these studies described above support the negative associations of incense burning and neurodevelopment among children 13–15 …”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…In the present study, children who occasionally and frequently exposed to incense fume performed inferior performance on executive function than nonusers. The findings of our study combining the results of these studies described above support the negative associations of incense burning and neurodevelopment among children 13–15 …”
Section: Discussionsupporting
confidence: 86%
“…We were aware of only three studies investigating the neurodevelopmental effects of incense burning. [13][14][15] More specifically, in a birth cohort study in Taiwan, infants occasionally and persistently exposed to incense smoke at both 6 and 18 months of age exhibited delay in gross motor neurodevelopment milestone including walking with support and walking steadily, and there were more evident associations in the persistent exposure group (e.g., walking with support, OR: 1.26 (95% CI: 1.08-1.47), HR: 1.07 (95% CI: 1.03-1.11) in the occasionally exposed group, OR: 1.24 (95% CI: 1.06-1.45), HR: 1.11 (95% CI: 1.07-1.16) in the persistent exposure group). 13 Data from the same study on preterm infants showed that household incense burning exposure contributed to delayed achievement in walking with support (HR, 95%CI: 1.19, 1.01-1.39) and walking steadily (HR, 95%CI: 1.25, 1.06-1.47), especially for participants whose mothers had lower education level.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations